β-Arrestin1/miR-326 Transcription Unit Is Epigenetically Regulated in Neural Stem Cells Where It Controls Stemness and Growth Arrest - Agnese Po; Federica Begalli; Luana Abballe; Vincenzo Alfano; Zein Mersini Besharat; Giuseppina Catanzaro; Alessandra Vacca; Maddalena Napolitano; Marco Tafani; Felice Giangaspero; Franco Locatelli; Elisabetta Ferretti; et al. (Stem Cells International)
Cell development is regulated by a complex network of mRNA-encoded proteins and microRNAs, all funnelling onto the modulation of self-renewal or differentiation genes. How intragenic microRNAs and their host genes are transcriptionally coregulated and their functional relationships for the control of neural stem cells (NSCs) are poorly understood. We propose here the intragenic miR-326 and its host gene β-arrestin1 as novel players whose epigenetic silencing maintains stemness in normal cerebellar stem cells. Such a regulation is mediated by CpG islands methylation of the common promoter. Epigenetic derepression of β-arrestin1/miR-326 by differentiation signals or demethylating agents leads to suppression of stemness features and cell growth and promotes cell differentiation. β-Arrestin1 inhibits cell proliferation by enhancing the nuclear expression of the cyclin-dependent kinase inhibitor p27. Therefore, we propose a new mechanism for the control of cerebellar NSCs where a coordinated epigenetic mechanism finely regulates β-arrestin1/miR-326 expression and consequently NSCs stemness and cell growth.